Patients' Adherence to Anti-diabetic Medications and Associated Factors in Mizan-Tepi University Teaching Hospital: A Cross-Sectional Study - Jafer Siraj BPharm, MSc; Turi Abateka BPharm; Oliyad Kebede BPharm, MSc (SAGE Publishing, 2021)
Introduction: A number of medications have been demonstrated to lower blood glucose. However, current-day management has failed to achieve and maintain the optimal glycemic level for diabetic patients. Patients' non-adherence is among the most contributing factors. Therefore, the aim of this study was to explore the prevalence of non-adherence to anti-diabetic medications and associated factors. Methods: A hospital based cross-sectional study was conducted from November 2020 to January 2021. A systematic random sampling technique was used. Data were collected by structured questionnaire adapted from different literatures. Then, data were entered into SPSS version 25 and analyzed. To determine the association of dependent and independent variables, multiple logistic regression was done. P-value <.05 was considered statistically significant. Results: A total of 275 study participants were interviewed with a response rate of 100%. From this 53.8% were females, 59.3% were in the age group of 41-60 years, 35.3% were college/university graduates and 79.3% were not using social drugs. One hundred eighty-seven (68%) of them were adherent to their anti-diabetic medication. Factors found to be significantly associated with anti-diabetic medication adherence were age >60 years (AOR = .276, 95% CI = .124-.611) attending higher education (AOR = 6.203, 95% CI = 1.775-21.93), retired (AOR = 7.771, 95% CI = 1.458-41.427), housewife (AOR = 7.023, 95% CI = 1.485-33.215), average monthly income 1001birr-2000 birr (AOR = .246, 95% CI = .067-.911) and social drug use (AOR = 3.695, 95% CI = 1.599-8.542). Forgetfulness, not affording, side effects, misunderstanding of instructions, and poly-pharmacy were identified reasons for non-adherence. Conclusions and Recommendations: Patients' adherence to anti-diabetic medications in the current study is sub-optimal. Age, monthly income, level of education, occupational status, and social drug use were associated with adherence. Forgetfulness, not affording, and side effects were reasons identified to contribute to non-adherence. Therefore, adherence counseling, use of alarms, and the way to mitigate non-affordability, including anti-diabetic medications into a program drug should be considered.